Hubungan Pengetahuan Dan Motivasi Terhadap Kepatuhan Minum Obat Pada Pasien TB Paru Di RSUP. H. Adam Malik Medan Tahun 2022 - Labora Br Manulang; Dina Afriani; Petra Diansari Zega; Lisdayanti Simanjuntak; Damayanty S; Kathrin Abella Saragih (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2022)
Pulmonary tuberculosis is an infectious infectious disease caused by bacteria, which can attack the respiratory system, namely the lungs. This disease annually contributes to the highest mortality in the world, including one of developing countries. To achieve successful treatment, patients must patiently take TB drugs thoroughly. There are several factors that influence the failure of treatment, namely from the patient himself, education, knowledge, and other social support. The purpose of this study was to determine the relationship of knowledge and motivation to adherence to taking medication for pulmonary tuberculosis patients in hospitals. H.Adam Malik in 2020.This type of research is descriptive correlation with cross sectional research design. The number of samples was 31 from April to June 2020. The research was conducted at RSUP. H. Adam Malik at TB Polyclinic. Bivariate analysis using the chi-square test to determine the relationship of Knowledge and Motivation to medication adherence in pulmonary TB patients. Based on a hypothesis test using chi-square with a confidence level of 95%, there was no significant relationship between knowledge and medication adherence (p = 0.473). There was a significant relationship between motivation and medication adherence (p = 0.001). The conclusion of this study is that there is no relationship of knowledge with adherence to taking medication and there is a relationship of motivation with adherence to taking medication in TB patients.